An Entity Theory of Intelligence Predicts Higher Cortisol Levels When High School Grades Are Declining - Lee, Hae Yeon (Child Dev, 2018)
Grades often decline during the high school transition, creating stress. The present research integrates the biopsychosocial model of challenge and threat with the implicit theories model to understand who shows maladaptive stress responses. A diary study measured declines in grades in the first few months of high school, salivary cortisol (N=360 students, N= 3,045 observations) and daily stress appraisals (N=499 students, N= 3,854 observations). Students who reported an entity theory of intelligence (i.e. the belief that intelligence is fixed) showed higher cortisol when grades were declining. Moreover, daily academic stressors showed a different, lingering effect on the next day’s cortisol for those with different implicit theories. Findings support a process model through which beliefs affect biological stress responses during difficult adolescent transitions.